Financial ratio analysis to Assess the Performance of Telecommunications Companies Listed on the Indonesia Stock Exchange 2017-2019 - Nurin - Jaslinah; Karnowahadi - Karnowahadi; Paniya - Paniya (JOBS (Jurnal Of Business Studies), 2020)
This study aims to assess the company's financial performance using financial ratio analysis of Telecommunications companies listed on the Indonesia Stock Exchange 2017- 2019 period. The sampling technique used was purposive sampling so that selected in this study PT Telekomunikasi Indonesia (Persero) Tbk, PT XL Axiata Tbk, PT Indosat Tbk and PT Smartfren Tbk, The type of data used in this study is secondary data which includes data on annual financial statements from 2017 to 2019. The analysis tool use the analysis of liquidity ratios, solvency and profitability. The results of the study were reviewed from the liquidity ratio using the current ratio and quick rasio, then the highest level of ratio obtained from 2017 to 2019 was PT Telekomunikasi Indonesia (Persero) and the lowest was PT Smartfren Tbk, however, the four companies produce ratios from 2017-2019 under the ratio valuation standard. This shows that the company's performance is not healthy because the company is unable to guarantee its current debt with its total current assets (liquid). The solvency ratio from the calculation debt to asset ratio shows that PT Telekomunikasi Indonesia (Persero) Tbk has the lowest ratio compared to other companies from 2017 to 2019, but out of all of the surveyed telecommunications companies show the results of the ratio exceeds the standard solvency ratio so the company is in a bad condition. Having a solvency ratio that is getting higher every year is feared that the company will not be able to guarantee long-term debt with the total assets it has (insolvable). Profitability ratios generated in telecommunications companies that were studied by calculating economic profitability/ return on investment and profitability of their own capital/ return on equity showed that the performance of companies that experienced a decline in profits from 2017 to 2019, even Smartfren suffered losses for three years in a row. This shows the company's performance in a bad condition